2020
DOI: 10.1249/mss.0000000000002388
|View full text |Cite
|
Sign up to set email alerts
|

Motor Competence, Physical Activity, and Fitness across Early Childhood

Abstract: Objectives To examine if the associations between motor competence and physical activity and musculoskeletal fitness change over time, whether motor competence is associated with longitudinal trajectories of physical activity and fitness, and mediating pathways among these constructs across early childhood. Methods Four hundred and eighteen children 3 to 5 yr of age (210 boys; age, 4.5 ± 1.0 yr) were recruited and completed three annual assessments as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
2
25
1
2
Order By: Relevance
“…Also, even though Schmutz et al [57] identified MC as a determinant of objectively measured PA 12 months later, MC at baseline was not significantly associated with change in either total PA or MVPA from baseline to follow-up. In contrast, a recent study in Canadian children aged 3-5 years reported that MC was a positive predictor of musculoskeletal fitness and vigorous PA over time and that better MC was associated with steeper increases in PA across time [78]. Yet in this study, there were no cross-sectional associations between objectively measured vigorous PA and MC when children were 3 years old.…”
Section: Physical Activitycontrasting
confidence: 94%
“…Also, even though Schmutz et al [57] identified MC as a determinant of objectively measured PA 12 months later, MC at baseline was not significantly associated with change in either total PA or MVPA from baseline to follow-up. In contrast, a recent study in Canadian children aged 3-5 years reported that MC was a positive predictor of musculoskeletal fitness and vigorous PA over time and that better MC was associated with steeper increases in PA across time [78]. Yet in this study, there were no cross-sectional associations between objectively measured vigorous PA and MC when children were 3 years old.…”
Section: Physical Activitycontrasting
confidence: 94%
“…Similarly, ambiguous results were seen for speed‐agility assessments, when reallocating LPA and sleep. It is well‐known that musculoskeletal fitness is an important indicator of health in childhood 3 and is particularly relevant in early childhood, owing to the short, intermittent nature of their activity 34 . It is also important to consider that for tests such as speed/agility and standing long jump, there is likely greater variability in movement patterns for preschoolers, as their neuromuscular system is less well developed.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a pattern may become more obvious for older children. A recent longitudinal study 34 across early childhood showed consistency in the strength of the association between motor competence and fitness, suggesting that these variables will continue to be associated over a longer follow‐up period, and may only become strongly associated once children reach middle to late childhood. In this sense, the results of this paper need to be considered respective to the population that is examined.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of regular physical activity (PA) for children’s health range from short-term fitness to long-term potential for reducing the incidence of chronic diseases that manifest in adulthood. Studies have documented that a regimen of 60 min of moderate-to-vigorous physical activity (MVPA) each day is positively associated with physical health status, fundamental motor skills [ 1 , 2 ], bone health [ 3 , 4 , 5 , 6 ], cognitive function [ 7 , 8 , 9 ], and socio-emotional development of children [ 9 , 10 , 11 , 12 ]. Nevertheless, despite the global effort to improve the health of young people, 80 percent of children and young people worldwide remain physically inactive or do not meet the recommended level of PA daily [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%